Comparing the use of phacoemulsification and combined surgery in angle-closure glaucoma. (3rd September 2017) - Teoh, CS; Aquino, MC; Loon, SC; Chew, P; Koh, V
ABSTRACT: Introduction : This review compared phacoemulsification alone versus combined phacoemulsification with glaucoma filtration surgery in the surgical management of angle-closure glaucoma. Areas covered : Phacoemulsification alone is generally safe with good predictable outcomes in angle-closure eyes. Studies have shown phacoemulsification alone significantly and sustainably reduces IOP in angle-closure eyes. In eyes with primary angle-closure and primary angle-closure glaucoma, the EAGLE study showed the superior efficacy and safety profile of lens extraction compared to laser iridotomy. Combined phacotrabeculectomy has the potential to achieve better IOP reduction and it is particularly useful in patients with advanced glaucoma. However, it carries higher ocular morbidity and long-term complications. Expert commentary : The surgical approaches of either phacoemulsification alone or combined phacotrabeculectomy in angle-closure eyes depends on the lens status, classification of angle-closure and the severity of the glaucoma. The efficacy and safety profile of each surgical approach have to be weighed against risks and severity of disease. Combining phacoemulsification with glaucoma drainage implant is safe with good surgical outcomes and could be an alternative to phacotrabeculectomy. Combining phacoemulsification with micro-invasive glaucoma surgery may have a role in the management of early primary angle closure but further studies are required to provide supporting evidence.